Design and Implementation of a Low-cost IoT-based SCADA System using ESP32 - Johari, Mohammad Amin; Chew Chang Choon (Evolution in Electrical and Electronic Engineering, 2023)
First, temperature is one of the most monitored variables in many commercial and industrial settings. Temperature sensors used in the Internet of Things (IoT) are typically relatively small, require very little power, and can gauge relative humidity. In an Internet of Things system, it is necessary to acquire temperature information that is both timely and accurate. The performance of an Internet of Things temperature system is compared with that of an industrial temperature system in this paper. In this project, an Internet of Things temperature monitoring system has been created by combining a Raspberry Pi with a DHT11 temperature sensor to simulate an Internet of Things temperature monitoring system. The primary purpose of this report is to design an Internet of Things (IoT)–based ESP32 device that can monitor environmental parameters and provide details regarding its implementation. It also offers knowledge regarding the Internet of Things and other potential solutions for this project. In addition to using the finished prototype, this report analysed several possible approaches. The Internet of Things temperature monitoring system that uses the DHT11 sensor offers accurate measurements up to degrees Celsius but has a slower response time when it comes to detecting temperature changes. This discovery could be a reference point when designing an Internet of Things system that incorporates temperature monitoring.